Study the work shown below and compare the results to the product of –2i(6 – 7i). (0 – 2i)(6 – 7i) = (0)(6) + (0)(–7i) + (–2i)(6) + (–2i)(–7i) = 0 + 0 –12i + 14i2 = –12i – 14 = –14 –12i The products are

Respuesta :

-2i (6 - 7i)
 The first thing we must do is to solve this product and then compare it with the work shown.
 Resolving we have
 -2i (6 - 7i)
 (-2i) * (6) + (-2i) * (- 7i)
 -12i + 14i ^ 2
 -12i - 14
 Comparing, we can say that the products are the same.
 answer:
 the products are the same.

the answer is *Equal*.

Otras preguntas

ACCESS MORE